Porphyrin-based frameworks for oxygen electrocatalysis and catalytic reduction of carbon dioxide - Liang, Zuozhong; Wang, Hong-Yan; Zheng, Haoquan; Zhang, Wei; Cao, Rui (Chemical Society reviews, 2021)
Porphyrin-based frameworks, as specific kinds of metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), have been widely used in energy-related conversion processes, including the oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and CO 2 reduction reaction (CO 2 RR), and also in energy-related storage technologies such as rechargeable Zn-air batteries. This review starts by summarizing typical crystal structures, molecular building blocks, and common synthetic procedures of various porphyrin-based frameworks used in energy-related technologies. Then, a brief introduction is provided and representative applications of porphyrin-based frameworks in ORR, OER, Zn-air batteries, and CO 2 RR are discussed. The performance comparison of these porphyrin-based frameworks in each field is also summarized and discussed, which pinpoints a clear structure-activity relationship. In addition to utilizing highly active porphyrin units for catalytic conversions, regulating the porous structures of porphyrin-based frameworks will enhance mass transfer and growing porphyrin-based frameworks on conductive supports will accelerate electron transfer, which will result in the improvement of the electrocatalytic performance. This review is therefore valuable for the rational design of more efficient porphyrin-based framework catalytic systems in energy-related conversion and storage technologies. The recent progress made on porphyrin-based frameworks and their applications in energy-related conversion technologies ( e.g. , ORR, OER and CO 2 RR) and storage technologies ( e.g. , Zn-air batteries).